ANALISIS KELAYAKAN KARYAWAN DALAM PENGAJUAN PINJAMAN MENGGUNAKAN METODE K-MEANS CLUSTERING PADA KOPERASI PRIMER TUT WURI HANDAYANI - Iwan Nugroho, - (2019)
This research was made due to help the head of cooperative shop in taking desicions of primary Tut Wuri Handayani cooperative shop's employees worthiness so this can avoid some employees to have financial problems. K-Means Clustering method is used in this employees' worthiness analysis proccess. The method is able to analyze several possibilities which happen based on 4 criterias such as Times of Service, Category, Salary, and Amount of Loan. In this research, writer analyzed and executed K-Means Clustering method using Rapidminer to get a selection result by classifying 2 Clusters. Data collection was done by literature studies, observation, and interview. The result of this research is Analysis of Employees' Worthiness in Submitting a Loan using K-Means Clustering Method in The Primary Cooperative Shop Tut Wuri Handayani. Writer acquired results that from 40 datas of Tut Wuri Handayani Employees, they obtained 13 items that classified in to Cluster 0 which means they are worthy to have loan, and 27 items that classified in to Cluster 1 which means they are not worthy to have loan